A radical cascade reaction triggered by thiyl radical; an approach toward synthesis of tricyclic structure of platensimycin. (1st February 2016) - Kamimura, Akio; Kawakami, Yusuke
GRAPHICAL ABSTRACT: ABSTRACT: The formation of oxa-tricyclic core of platensimycin was attempted. A key precursor of radical cyclization, cyclic anhydride, was readily prepared from diethylmalonate in 6 steps in good yields. Obtained precursor, diallylmethylene-δ-lactone, underwent radical cascade reaction triggered by thiyl radical, giving bicyclic ether in a stereoselective manner.